Prevalence of Mycoplasma gallisepticum and Mycoplasma synoviae in free range chickens and wild birds in Osun, Oyo and Kwara States, Nigeria (2022)
Mycoplasma gallisepticum and Mycoplasma svnoviae are pai ho gens of thè class mollicutes thatpose economie and veterinary health concerns amongpoultryfarmers and veterinary agencies. Listedby thè World Organisation far Animai Health (OIE), these pathogens are responsible far various degrees of clinical manifestations in poultry, wild birds and other free-living birds. This study was designedto examine thè prevalence of Mycoplasma gallisepticum and Mycoplasma yynoviae infection among free-range chickens and wild birds in selected States in Nigeria. Using rapid Mycoplasma field agglutination piate test as well as culture, we examined 541 blood samples collected from free-range (n = 501 ) and wild birds (n = 40), in three States in Nigeria; Osun, Oyo and Kwara States. Overall, thè free-range chickens were positive for both M. gallisepticum and M. synoviae antibodies, while thè wild birds were positive for only A4. synoviae antibodics. Rcsuits showed that 134 (24.7%) and 367 (73.3) frcc-rangc chickcns wcre positive l'or M. galliseplicum and M. synoviae rcspectivcly, \vhilc 13 (32.5%%) wild birds wcre positive for A4. synoviae. Kwara State had thè highest number of M. galliseplicum (87; 23.6%) and M. synoviae (290; 78.6%) seropositive cascs, while Osun (34; 28.8%) had thè highest seroprcvalencc of M. galliseplicum inlection. Rcsuits from culture showed that isolatcs of Mycoplasma wcre obtaincd in 46 of thè 541 samplcs taken. fhus, a detection rate of 8.5% was obtaincd. Furthermorc, these isolatcs wcre obtaincd from both thè frcc-rangc chickcns and the wild birds. Detection of antibodics to Mycoplasma shown in this sludy suggcsl inlection of thè frcc rango locai and wild birds by Mycoplasma; these birds could bc possiblc sourccs of inlection lo commercial poullry birds.